Desert Mountain Sea - "Leather, Sue" (Oxford University Press: Oxford, 2001)
A collection of three adventure stories describing three determined women and their tough, lonely and dangerous journeys. Robyn Davidson walks through miles of desert, Arlene Blum survives a climb on one of the highest peaks in the world, and Naomi James sails around the world alone on a journey of more than 250 days.